2020
DOI: 10.3389/fonc.2020.01657
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Estrogen and Progesterone Axis in Cancer Stemness: Elucidating Molecular Mechanisms and Clinical Significance

Abstract: Estrogen and progesterone regulate the growth and development of human tissues, including the reproductive system and breasts, through estrogen and progesterone receptors, respectively. These receptors are also important indicators for the clinical prognosis of breast cancer and various reproductive cancers. Many studies have reported that cancer stem cells (CSCs) play a key role in tumor initiation, progression, metastasis, and recurrence. Although the role of estrogen and progesterone in human organs and var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 181 publications
(227 reference statements)
0
5
0
Order By: Relevance
“…Estrogens are essential for human health and have broad biologic mechanisms of action such as regulating reproductive processes and the development and homeostasis of a wide range of tissues and organs, as well as playing a crucial role in the cardiovascular, nervous, immune systems, and bone metabolism [ 13 ]. In addition, tumor expression of hormone receptors plays an important role as an indicator of clinical prognosis of breast and genito-urinary cancers [ 14 ]. It has been reported that in patients with MPM, tumor expression levels of the estrogen receptor beta (ERβ) as assessed by immunohistochemistry (IHC) are correlated with survival [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Estrogens are essential for human health and have broad biologic mechanisms of action such as regulating reproductive processes and the development and homeostasis of a wide range of tissues and organs, as well as playing a crucial role in the cardiovascular, nervous, immune systems, and bone metabolism [ 13 ]. In addition, tumor expression of hormone receptors plays an important role as an indicator of clinical prognosis of breast and genito-urinary cancers [ 14 ]. It has been reported that in patients with MPM, tumor expression levels of the estrogen receptor beta (ERβ) as assessed by immunohistochemistry (IHC) are correlated with survival [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, considerable progresses have been made in BC treatment, especially through the introduction of targeted therapies against the signaling pathways governing cancer onset and progression [ 33 35 ]. For instance, ER, PR and HER2 play key roles in the evolution of the majority of BCs, and selective targeting of these proteins has enabled the inhibition of their associated pathways, leading to a better prognosis for tumors that are positive for these receptors [ 36 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…60 In addition, it has been reported that estrogen regulates the SC of the human reproductive system, which induces SC proliferation and participates in the regulation of SC populations in a paracrine manner. 61 In summary, we have analyzed the expression of SC/TSC markers at different stages of hyperplastic/adenomatous pituitary development. It was demonstrated that there was an increase in protein levels at the beginning of the tumoral process for GFRa2, Nestin, CD44 and CD133, with a different distribution of the SC/TSC niche being predominant in the adenomatous AP, probably acting as a reservoir in terms of the origin of the differentiated cells that later composed the adenoma mass.…”
Section: Discussionmentioning
confidence: 99%